PERANAN YAYASAN PANTI ASUHAN AL FHAT SEBAGAI WALI ATAS ANAK ASUHAN DITINJAU DARI SEGI HUKUM DI PEKANBARU - Fahasta, Tiara Purnama; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Guardianship is a person acting in lieu of the parent of a child who is immature because the child's parent dies or the limitation of ability in the economy or the right of the caregiver of the parent to be revoked by the court due to legal consequences. For that the role of orphanage foundation is very influential in the survival of children caused by these factors. As regulated in Law Number 35 Year 2014 in Article 33 paragraph 1 that in the case of a parent the child is incapable of performing legal acts or unknown residence or whereabouts, then a person or legal entity that meets the requirements may be appointed as the guardian of the child concerned .Based on the problems as mentioned above, the authors conduct research at Al Fhat Orphanage Foundation with the aim of research: a. To determine the role of the Al Fhat orphanage in overcoming the legal guardianship issues b. To know the legal consequences caused by the appointment of guardianship to foster children not through the determination of the court.Viewed from the point of the method used, this research is classified in the type of research socioligis juridisi namely sociological juridical is an attempt to examine the effect of the validity of positive law on the life of the community by looking at the real circumstances that exist in society because in this study the authors directly conduct research on Foundation Orphanage Al Fhat while viewed from the nature of this research is Descriptive.Summarizing the content of this research, it can be concluded that the Al Fhat orphanage in receiving foster children does not meet the requirements of the law such as the establishment of the court in accepting the foster children because the foster children are accepted based on the submission of parents or substitutes of the child's parents and attaching the poverty certificate from the residence. Thus the Al Fhat orphanage can be said or classified as a social worker.Key words: Role-Guardianship-Orphanage